Analyzing Hotel Owners Acceptance of Tiket.com Using Technology Acceptance Model - Baiq Dwi Zulianti Kurrotaa'yun; Noor Alamsyah; Helmina Andriani; Santi Ika Murpratiwi (Jurnal Nasional Pendidikan Teknik Informatika : JANAPATI, 2024)
Lombok, a captivating island in West Nusa Tenggara, faces tourism challenges due to the COVID-19 pandemic, causing a decline in visits and revenue. Senggigi, known for its picturesque beaches, experienced a drastic drop in hotel occupancy. Focusing on post-pandemic recovery, the aim of this research is to investigate the adoption of Tiket.com applications by hotel owners in Senggigi, utilizing the Technology Acceptance Model (TAM) with a Partial Least Squares (PLS) approach. This research method is using a quantitative methodology, the study involves 50 respondents from 20 hotels, distributing questionnaires to explore perceptions of Online Travel Agent technology adoption based on TAM variables. The result of this research is the Partial Least Squares analysis indicates that perceived ease of use significantly influences perceived usefulness, emphasizing the importance of a user-friendly platform. While perceived usefulness alone may not directly impact usage intention, positive attitudes toward the system play a crucial role. The study recommends collaborative efforts between Tiket.com service providers and Senggigi hotel owners to enhance system adjustments, aligning with user needs and expectations. This research contributes valuable insights into technology's role in post-pandemic tourism recovery, providing a nuanced understanding of factors influencing the acceptance of Tiket.com within the Senggigi hospitality sector.